Group creativity and personality traits among Malaysian product design students / Wan Zaiyana Mohd Yusof and Amer Shakir Zainol - Mohd Yusof, Wan Zaiyana; Zainol, Amer Shakir (Research Management Institute (RMI), 2010)
Brainstorming is a series of procedures (rules) designed to maximize the productivity of groups engaged in idea generation by reducing process losses, popularized by Osborn an advertising executive. This technique is always used by an organization in industrial design context. Students in industrial design are also exposed with this technique to generate the creative ideas. The main concern in this tool is increasing creativity in organization. This study examines the effects of personality traits on, evaluation apprehension among students in group brainstorming. Using a quasi experimental research design, 460 university students from 6 different universities have participated in this study. The hypotheses of this study are tested using Partial Least Squares (PLS). Results reveal that of the three personality traits, Extraversion, emotional stability, and openness are negatively significant related to the evaluation apprehension. The results are of potential interest to industrial design context, educators, and researchers. Also this study responds to call for further brainstorming research.